Motivasi, Lingkungan Keluarga, Biaya Pendidikan, Peluang Kerja dan Minat Mahasiswa Melanjutkan PPAk - Kesumawati, Ni Luh Putu Diah; Widanaputra, Anak Agung Gde Putu (E-Jurnal Akuntansi; Vol 33 No 3 (2023)DO - 10.24843/EJA.2023.v33.i03.p08, 2023)
The research objective was to obtain empirical evidence of the influence of motivation, family environment, educational costs, and job opportunities on the interest of S1 Accounting Students to continue Accounting Professional Education (PPAk). This research was conducted at the Faculty of Economics and Business, Udayana University. The number of samples used was 67 samples, with the nonprobability sampling method using purposive sampling technique. Data collection was carried out using a questionnaire. The analysis technique used is multiple linear regression analysis technique. The results of the analysis found that career motivation was positively related to students' interest in continuing PPAk; economic motivation is positively related to students' interest in continuing PPAk; family environment has a positive effect on students' interest in continuing PPAk; education costs have a negative effect on students' interest in continuing PPAk; and job opportunities have a positive effect on students' interest in continuing PPAk. Keywords: Motivation; Family environment; Cost of education; Job Opportunities; Student Interest